Materials and design in green building for sustainable constructions - Siew, Huey Ting; Abu al-Rejal, Hussein Mohammed (2015)
In this globalization era, sustainable constructions turn into the key to stimulate green building practice.One of the notable ways in practicing green building is through conservation of materials and resources and sustainable design of the building itself. Building materials and methods that are originally used have given rise to problems related to the environment and human’s health.In Malaysia, people are less aware about green building and they have minimum understanding and know-how about green materials and sustainable design.Therefore, this study aims to explore building materials and design employed in green buildings to achieve sustainability and to identify the benefits of utilizing green materials and sustainable design. This study was carried out using a case of construction sector in Malaysia.The data were collected via an interview with Eco World Development Sdn Bhd. The company utilizes materials like polyvinyl chloride (PVC) for water and cable work installations, laminated timber and porcelain or ceramic tiles as flooring, creeper plants as the insulation material, and bricks and reinforced concrete for interior wall construction.The company also involves in recycle practice by reusing the form work in constructing the buildings.In addition, Eco World Development Sdn Bhd focuses on passive design such as cross ventilation and solar shading to reduce energy consumption.Due to time constraint, there is only one company that has been interviewed.It is recommended that more property development companies should be interviewed in order to obtain more comprehensive results.